Examining the Relationship Between Ethical Climate, Workplace Bullying, Organizational Justice, and Academic Job Satisfaction Among Criminology Instructors - Rojas, Erika Grace; Nabe, Nestor (Journal of Interdisciplinary Perspectives, 2025)
This study explored the relationship between ethical climate, workplace bullying, organizational justice, and academic job satisfaction among criminology instructors in CARAGA and Northern Mindanao, Philippines. Employing a non-experimental quantitative research design, data were gathered from 400 randomly selected full-time criminology instructors using a validated and modified survey instrument. Structural Equation Modeling (SEM) was utilized to examine the predictive relationships among variables. Results revealed a very high level of ethical climate, workplace bullying, and academic job satisfaction, along with a high level of organizational justice. The findings demonstrated statistically significant relationships among all variables, with ethical climate, workplace bullying, and organizational justice exerting positive and significant effects on academic job satisfaction. These findings offer critical implications for higher education institutions and policymakers. Strengthening the ethical climate and ensuring organizational justice can serve as strategic interventions to enhance instructor satisfaction and retention in criminology programs. Furthermore, the study emphasizes the importance of institutional policies that proactively prevent and address workplace bullying. The results contribute to the growing body of knowledge on organizational behavior in the academic setting. They may inform CHED and school administrators about the development of faculty-centered policies and a more supportive work environment.